Faktor Jumlah Nelayan dan Kapal dalam Menentukan Produksi Perikanan di Kabupaten Kutai Timur - Sulistianto, Erwan; Fahrizal , Wahyu; Sarifuddin, Andri (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
East Kutai Regency is one of the coastal regencies in East Kalimantan Province. The potential of marine fisheries resources is quite large and has a role in improving the community's economy. Fisheries production in East Kutai Regency is influenced by many factors, including the number of fishermen and the number of ships used. This study was conducted to determine how much influence the variables of the number of fishermen and the number of ships used have on marine fisheries production in East Kutai Regency. The method used is the regression analysis method. The results of the study revealed that, according to the t-test, the number of fishermen variable showed a t-value significantly lower than the critical value, indicating no significant impact on marine fisheries production in East Kutai Regency. Similarly, the number of ships variable also yielded a t-value below the critical threshold, further suggesting its negligible influence on production levels. Additionally, the F-test demonstrated that, when considered together, the number of fishermen and ships had an F-value well below the critical value, reinforcing the conclusion that these factors do not significantly affect marine fisheries production in the region. The implications of these findings suggest that factors such as the number of fishermen and ships may not be as influential in determining marine fisheries production in East Kutai as previously assumed. This could prompt further investigation into other potential variables, such as environmental conditions, technology, or fishing practices, which may have a more substantial impact on production. Policymakers and industry stakeholders may need to consider alternative strategies or focus on different factors to boost marine fisheries productivity in the region.